Desain didaktis berbasis multimodal learning dalam pembelajaran matematika siswa ditinjau dari gaya belajar - Shintia Permata Surachman; Herani Tri Lestiana; Darwan Darwan (Departemen Pendidikan Matematika, FPMIPA, UPI, 2024)
This research is motivated by the lack of technology-based media designs that consider potential learning barriers from the perspective of students' learning styles. The purpose of this study is to explore how didactical design and the implementation of a multimodal learning-based didactical design in social arithmetic materials can reduce learning barriers and improve students' learning outcomes based on their learning styles. The research method applied is Didactical Design Research (DDR), which involves three stages: prospective analysis, metapedadidactic analysis, and retrospective analysis. The results of this study include a Hypothetical Learning Trajectory (HLT) that was developed into an empirical didactical design aimed at improving students' learning outcomes. The developed didactical design consists of three sessions, each utilizing different media to accommodate students' various learning styles. Findings from this research indicate a reduction in students' learning barriers, with an average decrease of over 50%. Furthermore, students' learning outcomes improved after learning with the developed didactical design, achieving an n-gain score of 0.63.